2007
DOI: 10.1001/archsurg.142.8.708
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 80-Hour Workweek on Patient Care at a Level I Trauma Center

Abstract: Hypothesis:The 80-hour workweek limitation for surgical residents is associated with an increase in mortality and complication rates among adult trauma surgical patients.Design: Retrospective cohort study.Setting: Academic level I trauma center.Patients: Trauma patients admitted before and after the 80-hour workweek limitation.Methods: We compared death and complication rates for adult trauma patients admitted during a 24-month period before (2001)(2002)(2003) and a 24-month period after (2004)(2005)(2006) imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 32 publications
1
38
2
Order By: Relevance
“…Conversely, several studies have demonstrated an increase in complication rates and readmission rates on surgical wards after implementation of work-hour restrictions. 33,34 Poor communication, incomplete sign-over and decreased resident involvement in patient care were cited as primary factors.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, several studies have demonstrated an increase in complication rates and readmission rates on surgical wards after implementation of work-hour restrictions. 33,34 Poor communication, incomplete sign-over and decreased resident involvement in patient care were cited as primary factors.…”
Section: Discussionmentioning
confidence: 99%
“…Some academic centers have reported an association between increased surgical volumes and increased complication rates (10). We hypothesized that an optimal daily volume for CCs may exist at our academic training center.…”
Section: Original Articlementioning
confidence: 99%
“…Replacement of straightforward invasive diagnostic procedures by noninvasive imaging has further reduced the opportunities to acquire basic IR skills. Added to this, implementation of Working Time Directives (e.g., in the United States and Europe) has compounded the reduction in trainees' clinical experience [2,3]; yet it still takes a large number of procedures to approach proficiency (e.g., 300 in the case of coronary angiography) [4]. The apprenticeship model itself also lacks transparency, has potential for unfairness in trainee assessments, and assumes that experts are able to properly articulate their expertise, which is often not the case, particularly when inhibited by the presence of a conscious patient.…”
Section: Drawbacks Of Training Through Apprenticeshipmentioning
confidence: 99%
“…Indeed, the apprenticeship has been described as inefficient, unpredictable, and expensive [3,5,6], and its suitability for training has been questioned in the absence of a mechanism for measuring posttraining skill [7]. The modern medical education system clearly requires either a reliable, reproducible, and valid alternative, or a supplement to current training and assessment methods.…”
Section: Drawbacks Of Training Through Apprenticeshipmentioning
confidence: 99%